Structural Dynamics within Escherichia coli’s F1Fo ATP Synthase Complex - Britza Chavez-Arellano (UNC Test Journal, 2024)
The F1Fo adenosine triphosphate (ATP) synthase complex is a membrane-bound protein found in all domains of life that facilitates energy transduction through a fascinating rotary mechanism. ATP synthase has two motors, the F1 head, in which rotation of the central stalk catalyzes ATP synthesis, and the membrane-bound Fo motor complex, in which the electrochemical proton gradient drives c-ring rotation by proton movement through the subunit a stator. ATP hydrolysis can also drive proton pumping in the reverse direction. Recently, cryo-electron microscopy images have revealed the structure of the proton pathway and captured aspects of rotation and elasticity within the complex, but the mechanism of proton-driven rotation of the c-ring is not fully understood. Site-directed spin labeling coupled with electron paramagnetic resonance spectroscopy can reveal conformational changes within proteins. To observe structural dynamics of the subunit a stator in Fo, and the potential effect of the lipid environment, ATP synthase was purified in native-like environments using amphipathic polymer nanodiscs or reconstitution into proteoliposomes. Mobility of spin labels at several positions and under various biochemical conditions reveal differences in backbone dynamics in the two lipid environments.